Propuesta de mejoramiento del corredor ferroviario Coatzacoalcos-Salina Cruz - Posadas Alba, José Adolfo Raúl (Universidad Michoacana de San Nicolás de Hidalgo, 2010)
To manage a public works of a certain size, it takes many years and several events unfold; as occurred in deciding the construction of the road and railroad equipment Isthmus of Tehuantepec. Efforts back the government of President Antonio Lopez de Santa Anna, when given the first award, this happens in 1842, for the construction of trans-isthmus rail. Eleven years later, in 1853, another grant for the same purpose is granted. So concessions and contracts occur until 1894, when the railway line is finished in question. And for its operation in 1902, during the government of General Porfirio Diaz, a contract for 51 years with the firm Pearson is Concerta. That contract was never fulfilled, because they declared heavy losses and then the now President Venustiano Carranza, it terminates absorbing the losses by the official body Puerto Free Mexican which was valid until 1925, when he was transferred to the new National Railways body from Mexico. The railway, revolutionized the transport of cargo and passengers, replacing time-consuming walks of carts and pack animals, with the establishment of 17 national rail routes; among these it corresponded to the number 15 which would link Coatzacoalcos Veracruz to Salina Cruz, Oaxaca. Already in the 90's, in the privatization process, whose purchases were discriminatory, the Isthmus of Tehuantepec Railroad, was among non-preferred by buyers. Since prior to this event, in 1954, another series of events begins with the idea of ??rehabilitating or upgrading to double track the rail transisthmian. Recall that just Delfin Sanchez had given the construction thereof; Eduardo Mc Murdo, manages the contract for reconstruction.

Para gestionar una obra pública de cierta envergadura, transcurren muchos años y se desarrollan varios eventos; como los acontecidos para decidir la construcción de la vía y equipamiento del ferrocarril del Istmo de Tehuantepec. Las gestiones se remontan al gobierno del Presidente Antonio López de Santa Anna, cuando se da la primera concesión, esto sucede en el año 1842, para la construcción del ferrocarril transistmico. Once años después, en 1853, se concede otra concesión con la misma finalidad. Así se suceden concesiones y contratos hasta que en 1894, año en que queda concluido el tramo ferroviario en cuestión. Ya para su operación en 1902, durante el Gobierno del General Porfirio Díaz, se concreta un contrato por 51 años con la firma Pearson. Dicho contrato nunca se cumplió, debido a que declaraban pérdidas cuantiosas y entonces el ahora Presidente de la República Don Venustiano Carranza, lo rescinde absorbiendo las pérdidas mediante el organismo oficial Puerto Libres Mexicanos que tuvo vigencia hasta 1925, cuando fue transferido al nuevo organismo Ferrocarriles Nacionales de México. El ferrocarril, revolucionó el transporte de carga y pasaje, sustituyendo las tardadas caminatas de carretas y recuas, con el establecimiento de 17 rutas ferroviarias a nivel nacional; entre estas le correspondió el número 15 a la que enlazaría a Coatzacoalcos Veracruz con Salina Cruz Oaxaca. Ya en los años 90´s, en el proceso de privatización, cuyas compras fueron discriminatorias, el Ferrocarril del Istmo de Tehuantepec, quedó entre los no preferidos por las empresas compradoras. Desde antes de este acontecimiento, en el año de 1954, inicia otra serie de eventos con la idea de rehabilitar o modernizar con doble vía el ferrocarril transistmico. Recordemos que apenas Delfín Sánchez había entregado la construcción de éste; Eduardo Mc Murdo, logra el contrato para la reconstrucción.
Facultad de Ingeniería Civil. Maestría en Infraestructura del Transporte en la Rama de las Vías Terrestres
Keywords: info:eu-repo/classification/cti/7; FIC-M-2010-0049; Mejoramiento; Corredor; Ferroviario; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3062